2017
DOI: 10.1038/onc.2016.507
|View full text |Cite
|
Sign up to set email alerts
|

KLF6 depletion promotes NF-κB signaling in glioblastoma

Abstract: Dysregulation of the NF-κB transcription factor occurs in many cancer types. Krüppel-like family of transcription factors (KLFs) regulate the expression of genes involved in cell proliferation, differentiation and survival. Here, we report a new mechanism of NF-κB activation in glioblastoma through depletion of the KLF6 tumor suppressor. We show that KLF6 transactivates multiple genes negatively controlling the NF-κB pathway and consequently reduces NF-κB nuclear localization and downregulates NF-κB targets. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 61 publications
(82 reference statements)
1
26
0
1
Order By: Relevance
“…The only potential tumor suppressor gene being hypermethylated was KLF6 . KLF6 depletion was associated with various cancers and a potential role in SI-NET warrants further investigation 24 27 . Unfortunately, since only FFPE tissue was available, no analysis of KLF6-expression could be performed within this study.…”
Section: Discussionmentioning
confidence: 99%
“…The only potential tumor suppressor gene being hypermethylated was KLF6 . KLF6 depletion was associated with various cancers and a potential role in SI-NET warrants further investigation 24 27 . Unfortunately, since only FFPE tissue was available, no analysis of KLF6-expression could be performed within this study.…”
Section: Discussionmentioning
confidence: 99%
“… UN 64 NEFM KLF6 inhibits the malignant phenotype of GBM in vitro and upregulates neuronal marker NEFM. UP 65 SYNPR SYNPR is downregulated differently expressed genes (DEGs) in GBM tissue samples. Down 66 TMEM130 UN UN GABRA1 Upregulation of miR-155 in GBM could may downregulate GABRA1 which renders tumor cells unresponsive to GABA signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Krüppel‐like factor 6 ( KLF6 ), also known as Core promoter element‐binding (COPEB) protein, is a common nuclear transcription factor in mammalian cells that was originally cloned from human placenta tissue and rat liver star mesenchyme . Recent studies showed that KLF6 is deregulated in cancers such as glioblastoma, prostate cancer, hepatocellular carcinomas, and colorectal cancer . KLF6 has important roles in regulating multiple biological processes including cell cycle, apoptosis, and differentiation regulation in cancer cells .…”
Section: Discussionmentioning
confidence: 99%